2011
DOI: 10.31729/jnma.32
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of IV Iron Compared to Oral Iron for Increment of Haemoglobin Level in Anemic Chronic Kidney Disease Patients

Abstract: Introduction: Anemia is the most common finding in chronic kidney disease patients. Iron supplements are commonly prescribed for these patients with or without erythropoietin therapy by means of oral and intravenous iron. Both oral and intravenous irons have their own advantage and disadvantage, and the efficacy is also different. The objective of the study is to analyze the efficacy of oral and intravenous iron in chronic kidney disease patients on erythropoietin therapy, an erythropoiesis stimulating agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 14 publications
0
21
0
1
Order By: Relevance
“…11 g/ dL. 29,39 There was no statistically significant difference between patients treated with IV iron and oral iron preparations (RR, 1.65; 95% CI, 0.54-5.05).…”
Section: Secondary Outcomesmentioning
confidence: 93%
See 4 more Smart Citations
“…11 g/ dL. 29,39 There was no statistically significant difference between patients treated with IV iron and oral iron preparations (RR, 1.65; 95% CI, 0.54-5.05).…”
Section: Secondary Outcomesmentioning
confidence: 93%
“…[29][30][31][32][33][34][36][37][38][39] Hb concentration change from baseline was increased in the IV arm (mean difference, 0.33 [95% CI, 20.11 to 0.76] g/dL; 3 trials; 319 patients). 34, 35,37 Two trials including 164 patients reported the number of patients who reached Hb levels .…”
Section: Secondary Outcomesmentioning
confidence: 99%
See 3 more Smart Citations